Conformational characterization of human eukaryotic initiation factor 2 alpha: a single tryptophan protein - Sreejith, R. K.; Yadav, Viveka Nand; Varshney, Nishant K.; Berwal, Sunil K.; Suresh, C. G.; Gaikwad, Sushama M.; Pal, Jayanta K. (Biochemical and Biophysical Research Communications, 2009)
The alpha-subunit of the human eukaryotic initiation factor 2 (heIF2 alpha), a GTP binding protein, plays a major role in the initiation of protein synthesis. During various cytoplasmic stresses, eIF2 alpha gets phosphorylated by eIF2 alpha-specific kinases resulting in inhibition of protein synthesis. The cloned and over expressed heIF2 alpha, a protein with a single tryptophan (trp) residue was examined for its conformational characteristics using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The steady-state fluorescence spectrum, fluorescence lifetimes (tau(1) = 1.13 ns and tau(2) = 4.74 ns) and solute quenching studies revealed the presence of trp conformers in hydrophobic and differential polar environment at any given time. Estimation of the alpha-helix and beta-sheet content showed: (i) more compact structure at pH 2.0, (ii) distorted alpha-helix and rearranged beta-sheet in presence of 4 M guanidine hydrochloride and (iii) retention of more than 50% ordered structure at 95 degrees C. Hydrophobic dye binding to the protein with loosened tertiary structure was observed at pH 2.0 indicating the existence of a molten globule-like structure. These observations indicate the inherent structural stability of the protein under various denaturing conditions. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Circular dichroism; heIF2 alpha; K562 cells; Molten globule; Steady-state and time-resolved fluorescence

Conformational transitions of the catalytic domain of heme-regulated eukaryotic initiation factor 2 alpha kinase, a key translational regulatory molecule - Sreejith, R. K.; Suresh, C. G.; Bhosale, Siddharth H.; Bhavnani, Varsha; Kumar, Avinash; Gaikwad, Sushama M.; Pal, Jayanta K. (Journal of Fluorescence, 2012)
In mammalian cells, the heme-regulated inhibitor (HRI) plays a critical role in the regulation of protein synthesis at the initiation step through phosphorylation of a-subunit of the eukaryotic initiation factor 2 (eIF2). In this study we have cloned and performed biophysical characterization of the kinase catalytic domain (KD) of rabbit HRI. The KD described here comprises kinase 1, the kinase insertion domain (KI) and kinase 2. We report here the existence of an active and stable monomer of HRI (KD). The HRI (KD) containing three tryptophan residues was examined for its conformational transitions occurring under various denaturing conditions using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The parameter A and phase diagram analysis revealed multi-state unfolding and existence of three stable intermediates during guanidine hydrochloride (Gdn-HCl) induced unfolding of HRI (KD). The protein treated with 6 M Gdn-HCl showed collisional and static mechanism of acrylamide quenching and the constants (K-sv=3.08 M-1 and K-s=5.62 M-1) were resolved using time resolved fluorescence titration. Based on pH, guanidine hydrochloride and temperature mediated transitions, HRI (KD) appears to exemplify a rigid molten globule-like intermediate with compact secondary structure, altered tertiary structure and exposed hydrophobic patches at pH 3.0. The results indicate the inherent structural stability of HRI (KD), a member of the class of stress response proteins.
Keywords: Circular dichroism (CD); eIF2 alpha kinase; Heme-regulated inhibitor; Molten globule; Steady-state and time-resolved fluorescence

Cloning and characterization of trehalase: a conserved glycosidase from oriental midge, Chironomus ramosus - Shukla, Ekta; Thorat, Leena; Bendre, Ameya D.; Jadhav, Santosh; Pal, Jayanta K.; Nath, Bimalendu B.; Gaikwad, Sushama M. (3 Biotech, 2018)
Insect trehalase is a multiferous enzyme, crucial for normal physiological functions as well as under stress conditions. In this report, we present a fundamental study of the trehalase gene segment (1587 bp) from Chironomus ramosus (CrTre) encoding for 529 amino acids, using appropriate bioinformatics tools. C. ramosus, a tropical midge is an emerging animal model to investigate the consequences of environmental stresses. We observed that CrTre belongs to GH family 37 in the CAZy database and possess 57-92% identity to dipteran trehalases. In silico characterization provided information regarding the structural, functional and evolutionary aspects of midge trehalase. In the phylogenetic tree, CrTre clustered with the soluble dipteran trehalases. Moreover, domain functional characterization of the deduced protein sequence by InterProScan (IPR001661), ProSite (PS00927 and PS00928) and Pfam (PF01204) indicated presence of highly conserved signature motifs which are important for the identification of trehalase superfamily. Furthermore, the instability index of CrTre was predicted to be < 40 suggesting its in vivo stability while, the high aliphatic index indicated towards its thermal stability (index value 71-81). The modelled 3D tertiary structure of CrTre depicts a (alpha/alpha)(6) barrel toroidal core. The catalytic domain of the enzyme comprised Glu424 and Asp226 as the putative active site residues. Interestingly, the conserved motifs were observed to be formed by the flexible loopy regions in the tertiary structure. This study revealed essential sequence features of the midge trehalase and offers better insights into the structural aspects of this enzyme which can be correlated with its function.
Keywords: Conserved motifs; Homology modelling; Midges; Secondary structure; trehalose